Piriform Cortex Ablation Volume Is Associated With Seizure Outcome in Mesial Temporal Lobe Epilepsy. Issue 3 (24th September 2022) - Hwang, Brian Y.; Mampre, David; Tsehay, Yohannes K.; Negoita, Serban; Kim, Min Jae; Coogan, Christopher; Eremiev, Alexander; Palla, Adhith; Weber-Levine, Carly; Kang, Joon Y.; Anderson, William S.
Abstract : BACKGROUND: Growing evidence suggests that piriform cortex resection during anterior temporal lobectomy is important for achieving good seizure outcome in mesial temporal lobe epilepsy (mTLE). However, the relationship between seizure outcome and piriform cortex ablation during MR-guided laser interstitial thermal therapy (MRgLITT) remains unclear. OBJECTIVE: To determine whether ablation of piriform cortex was associated with seizure outcome in patients with mTLE undergoing MRgLITT. METHODS: We performed preablation and postablation volumetric analyses of hippocampus, amygdala, piriform cortex, and ablation volumes in patients with mTLE who underwent MRgLITT at our institution from 2014 to 2019. RESULTS: Thirty nine patients with mTLE were analyzed. In univariate logistic regression, percent piriform cortex ablation was associated with International League Against Epilepsy (ILAE) class 1 at 6 months (odds ratio [OR] 1.051, 95% CI [1.001-1.117], P = .045), whereas ablation volume, percent amygdala ablation, and percent hippocampus ablation were not ( P > .05). At 1 year, ablation volume was associated with ILAE class 1 (OR 1.608, 95% CI [1.071-2.571], P = .021) while percent piriform cortex ablation became a trend (OR 1.050, 95% CI [0.994-1.109], P = .054), and both percent hippocampus ablation and percent amygdala ablation were not significantly associated with ILAE class 1 ( P > .05). In multivariable logistic regression, only percent piriform cortex ablation was a significant predictor of seizure freedom at 6 months (OR 1.085, 95% CI [1.012-1.193], P = .019) and at 1 year (OR 1.074, 95% CI [1.003-1.178], P = .041). CONCLUSION: Piriform cortex ablation volume is associated with seizure outcome in patients with mTLE undergoing MRgLITT. The piriform cortex should be considered a high yield ablation target to achieve good seizure outcome.